Impact of YouTube on Non-verbal aspects of Pakistani ESL Learners’ Oral Presentation Skills - Hanif, Anum; Asgher, Tahira (Annals of Human and Social Sciences, 2024)
The current study aimed to determine the enhancement of Non-Verbal Aspects of Pakistani ESL learners’ Oral Presentation skills (OPSs) through YouTube. OPSs are the requisite part of Higher Education and play a significant role in developing learners’ professionalism. Employing a quasi-experimental approach, this study investigates the influence of YouTube videos on the non-verbal aspects of OPSs among ESL learners in Pakistan. Current research involved a convenient sample of 66 ESL learners enrolled at The Islamia University of Bahawalpur in Southern Punjab. The results of the study unveiled that YouTube is a productive educational tool for Pakistani ESL learners, contributing to the enhancement of their non-verbal aspects of OPSs. Improvements were noted in facial expressions, gestures, eye contact, body posture, and overall movement. This study recommends that Pakistani teachers must pay special attention towards the development of various aspects of learners’ Oral Presentation Skills in order to make them flourish professionally.